Pedestrian Trust in Automated Vehicles: Role of Traffic Signal and AV Driving Behavior - Jayaraman, Suresh Kumaar; Creech, Chandler; Tilbury, Dawn M.; Yang, X. Jessie; Pradhan, Anuj K.; Tsui, Katherine M.; Robert, Lionel P. (Frontiers in Robotics and AI, 2019)
Pedestrians’ acceptance of automated vehicles (AVs) depends on their trust in the AVs. We developed a model to promote pedestrians’ trust in AVs through implicit communications. To empirically verify this model, we conducted a human subject study with 30 participants in a virtual reality environment. The study manipulated two factors: AV driving behavior (defensive, normal, and aggressive) and the traffic situation (signalized and unsignalized crossing). Pedestrians’ trust in AVs was influenced by AV driving behavior as well as the condition/presence of a signal light. The impact of the AV’s driving behavior on trust in the AV was dependent on the presence of a signal light. There were also strong correlations between trust and pedestrian gaze at certain areas/objects. We also present implications for research and design.